RELIGIOSITAS PEZIARAH MAKAM MBAH PRIOK DAN KAITANNYA DENGAN PEMBELAJARAN IPS DI SMP MUHAMMADIYAH 14 JAKARTA - Indah Yulianti; Suswandari Suswandari; Lelly Qodariah; Nur Fajar Absor (STKIP Singkawang, 2024)
The aim of this research is to describe religiosity values and analyze the behavior of pilgrims to Mbah Priok's grave, the motivation of pilgrims and religiosity in relation to social studies values in social studies learning at SMP Muhammadiyah 14 Jakarta. The method used was a qualitative research method with a phenomenological approach, the research subjects included three key informants consisting of the grave administrator, two pilgrims, and one social studies teacher. The research results describe the role and function of religion in human life as a source of morals, instructions for truth, and spiritual guidance. The phenomenon of grave pilgrimage is a form of religious value. Social studies subjects are subjects that originate from the social life of society which are selected using social science concepts which are used for learning purposes in schools. Furthermore, research shows (1) religious behavior displayed by grave pilgrims is performing ablution, dhikr, wearing perfume, and tawasul; (2) the motivation that pilgrims have is religious motivation and being careful in praying; and (3) the values of religiosity are related to social studies learning which is integrated between religious and scholarly values which focuses more on social phenomena. This research concludes that Mbah Priok's grave pilgrim's religiosity is related to social studies scores in learning at SMP Muhammadiyah 14 Jakarta, reflected in the attitudes and behavior of students when praying, having to be pure, respecting, and appreciating people who have died.